Potential of Binahong Leaf Ethanol Extract (Anredera cordifolia (Ten.) Steenis) against Elevated HDL Levels (Rattus corvegious) Streptozonic-Induced Wistar Strain - Orbayinah, Salmah; Auliya, Rizqa (Universitas Muhammadiyah Yogyakarta, 2024)
Diabetes mellitus is frequently associated with decreased levels of high-density lipoprotein (HDL), which are prevalent cardiovascular disease risk factors. The use of synthetic drugs substantially increases the risk of atherosclerosis since they often have severe side effects, require high costs, and have poor prescription adherence. Anredera cordifolia (Ten.) Steenis, often known as the binahong plant, is a potentially effective complementary therapy for increasing HDL levels. Flavonoid compounds present in the ethanol extract of Binahong leaf have the potential to increase HDL levels. This work aims to evaluate the action of an ethanol extract from binahong leaves in raising HDL levels in rats of the Streptozotocin-induced Wistar strain (Rattus norvegicus). In this research, the Pretest-Posttest Control Group Design was used. The study involved the grouping of five Wistar strain rats (n=5) into five distinct groups: one received binahong leaf ethanol extract at concentrations of 25 mg/kg BW, 50 mg/kg BW, and 100 mg/kg BW, which served as the positive control group and received a negative control group supplemented with atorvastatin at 0.9 mg/kg BW. The CHOD-PAP method was applied to measure HDL levels. SPSS software was used to run the normality test, Wilcoxon test, one-way ANOVA test, and paired sample t-test. No statistically significant difference in HDL levels was found between treatment groups. The 50 mg/kg BW binahong leaf extract group had significantly higher HDL levels (p-value 0.05). As a result, the ethanol extract obtained from binahong leaves presumably raises HDL levels in streptozotocin-induced Wistar rats.